The Effect of Beneng Taro Flour (Xanthosoma undipes K. Koch) and Rice Bran (Oryza sativa L.) Substitution on the Physical and Sensory Characteristics of Bread - Winda Nurtiana; Zulfatun Najah; Mohamad Ana Syabana (Universitas Teuku Umar, 2023)
Beneng taro is an indigenous tuber from Banten which is rich of functional components such as dietary fiber and carotenoid pigments. So far, processing of beneng taro has not been developed. One of method to process it is to make into flour. Another material that is not utilized is rice bran. Rice bran is a by-product of rice milling which has only been used as animal feed, but the majority of functional components in rice accumulate in rice bran such as dietary fiber, oryzanol, and phytosterol compounds. The application of beneng taro flour and rice bran for food products can increase food diversification, beside of that it can reduce the use of wheat flour. The purpose of this study was to evaluate the effect of adding beneng taro flour and rice bran to bread on the physical and sensory characteristics. This study used a completely randomized design (CRD) with one factor, namely the ratio of wheat flour: beneng taro flour: rice bran (control, 65:30:5; 65:25:10; 65:20:15). This research was carried out in two repetitions. The result of this research were the increase of rice bran and the decrease of beneng taro flour substitution in bread decrease the expansion ratio, lightness (L*) of the crust and crumb, a* chromaticity of the crust, b* chromaticity of the crust and crumb, hue (oh) of the crust and crumb, and sensory acceptance. However, the increase of rice bran and decrease of beneng taro flour substitution increased density of dough, density of bread, and a* chromaticity of the crumb. Based on the results of sensory analysis, the bread with 65:30:5 formula was the best formula because it was close to the control.